1985
DOI: 10.1111/j.1365-2605.1985.tb00846.x
|View full text |Cite
|
Sign up to set email alerts
|

Laminin and type IV collagen in the human testis

Abstract: Specimens of normal human testis and biopsies from testes with Sertoli-cell-only syndrome in which the seminiferous tubules had a remarkably thickened lamina propria, were investigated immunohistochemically using specific antibodies against human laminin and human type IV collagen. In the normal testis, both laminin and type IV collagen were localized to the epithelial basement membranes and the peritubular cell layers. In addition, laminin was found in the Sertoli cells. In the pathological testis, structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 17 publications
2
15
0
Order By: Relevance
“…The testicular vasculature also exhibited intense laminin immunostaining, especially in the muscular layer of the medium sized vessels and in the basal lamina of the endothelium. These findings are consistent with numerous approaches that investigated the localization of laminin in the testis of several mammalian species including mouse (Pelliniemi and Frojdman 2001), rat (Gelly et al 1989;El Ouali et al 1991;Pelliniemi and Frojdman 2001), dog (Benazzi et al 1995) and human (Pollanen et al 1985;Davidoff et al 1990;Santamaria et al 1990;Virtanen et al 1997;Gülkesen et al 2002;Ooba et al 2008). Taken together, the localization of laminin in the testis of mammals and birds might point out to its crucial role in the male reproduction.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The testicular vasculature also exhibited intense laminin immunostaining, especially in the muscular layer of the medium sized vessels and in the basal lamina of the endothelium. These findings are consistent with numerous approaches that investigated the localization of laminin in the testis of several mammalian species including mouse (Pelliniemi and Frojdman 2001), rat (Gelly et al 1989;El Ouali et al 1991;Pelliniemi and Frojdman 2001), dog (Benazzi et al 1995) and human (Pollanen et al 1985;Davidoff et al 1990;Santamaria et al 1990;Virtanen et al 1997;Gülkesen et al 2002;Ooba et al 2008). Taken together, the localization of laminin in the testis of mammals and birds might point out to its crucial role in the male reproduction.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, El Ouali et al (1991) identified the laminin as being expressed in Sertoli cells during rat testicular development. These data may be partially substantiated by the fact that laminin is released from cultured rat Sertoli cells (Skinner et al 1985) and is synthesized and secreted by both Sertoli and peritubular cells in human (Pollanen et al 1985;Davis et al 1990;Richardson et al 1995). The lack of laminin immunoreactivity inside the seminiferous tubules of chicken, pigeon, and rabbits may suggest that laminin protein is not translated in Sertoli cells to a sufficiently high level to be detectable by immunohistochemistry.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The components of the extracellular matrix (ECM) of the human testis and their specific functions are not well‐known, but different collagen types, fibronectin, laminin (Pollanen et al. , 1985; Davidoff et al.…”
Section: Introductionmentioning
confidence: 99%
“…It is easily isolated and is often used to assess the biological role of ECMs, which have been shown to promote the adhesion of Sertoli cells [1], and to induce differentiation of some kinds of tumor cells [2]. The components of the seminiferous tubule extracellular matrix (ST-ECM) have been the subject of intense investigation, and the existence and/or localization of several components, such as fibronectin, laminin, entactin, SPARC, proteoglycans, and types I, III, and IV collagens have been documented [3][4][5][6][7][8][9][10][11]. However, many components of ECMs still remain to be investigated.…”
Section: Introductionmentioning
confidence: 99%